You Will Respect My Authoritah!? A Reply to Botting - Mizrahi, Moti (Informal Logic, 2019)
In a paper (Mizrahi 2013a) and a reply to critics (Mizrahi 2016a) published in Informal Logic, I argue that arguments from expert opinion are weak arguments. To appeal to expert opinion is to take an expert’s judgment that p is the case as (defeasible) evidence for p. Such appeals to expert opinion are weak, I argue, because the fact that an expert judges that p does not make it significantly more likely that p is true or probable, as evidence from empirical studies on expert performance suggests (Mizrahi 2016a, pp. 246-247). Unlike other critics of this argument (e.g., Seidel 2014 and Walton 2014), who take issue with the empirical evidence on expert performance, David Botting (2018) says that he wants to take issue with the premise that reliability is a necessary condition for the strength of appeals to expert opinion. I respond to Botting’s objections and argue that they miss their intended target. I also argue that his attempt to show that arguments from expert opinion are strong is unsuccessful.